Desain Closed-Loop Boost Converter Berbasis Voltage Lift Cell Untuk Implementasi Penguat Tegangan - Masramdhani Saputra; Asfari Hariz Santoso; Slamet Nurhadi; Imron Ridzki; Sri Wahyuni Dali (UPT - P2M POLINEMA, 2022)
In this new era the use of Photovoltaic (PV) is increasingly being used as an energy source. However, this technology has a drawback, namely, the intensity of the sun's light is always changing every time. This can cause the output voltage of the Photovoltaic (PV) Cell to be variable or indeterminate. In the Photovoltaic (PV) Cell, a dc-dc converter circuit is needed which functions to regulate and change the output of the Photovoltaic (PV) Cell. Conventional DC-DC boost converters are unable to provide a high step-up voltage boost due to the effects of switching power, rectifier diodes, and equivalent series resistance of inductors and capacitors. In this study, a closed loop design using a PID controller and analysis of a non-isolated boost dc-dc converter based voltage lift technique were carried out to achieve a high step-up voltage gain. In the presented converter two inductors, three capacitors and three power diodes are used. From this structure, this converter is referred to as a voltage lift cell-based boost converter. The structure of the presented converter is considered very simple, since it has only two stages of power. The voltage and current equations of each element with the converter voltage gain under continuous conduction mode (CCM) were extracted. In addition, the steady state analysis of the amplified stress and boundary conditions is discussed in this study. This boost converter circuit is simulated through the PSIM application. From the simulation results in the PSIM application, it is found that the boost converter circuit is able to increase the voltage from 100 V to 400 V and has an error value of 0. The specifications of the simulation results are a duty cycle of 0.6, and a frequency of 10,000 Hz.